A case of zoonosis ecthyma - Aliye Sağkan ÖZTÜRK; Hüseyin TOL; İsmail ŞEN (Eurasian Journal of Veterinary Sciences)
The aim of this case report is to show occurred the lesion a person's fingers that were formed after a lamb with a contagious ectima bites him. In routine clinical examination of lamp, small lesions mouth and around were observed along with high temperature. Lamb's the lower respiratory system was to be severely affected. There was also leucocytosis In lamb. Lesions on the fingers were diagnosed as orf by a physician.